The CUSTODIAN tool: simple design of home automation systems for people with special needs - José Martins Ferreira (2000)
The CUSTODIAN software tool is being developed within the scope of the CUSTODIAN project (Conceptualisation for User involvement in Specification and Tools Offering the Delivery of system Integration Around home Networks) and is funded by the E.U. The project consortium includes the European Installation Bus Association S.C. (EIBA). This paper focuses on the main characteristics of the software tool, which follow: Easiness of design of Home Automation Systems by professionals who may not have a specialised technical background, such as occupational therapists, project co-ordinators of housing associations, etc. Involvement of the client (elderly or disabled person) in the design process, through visual simulation of the system's functionality. Automatic translation of the design to an ETS project, providing an immediate implementation based on widely accessible EIB products.